Captación Y Colocación De Los Recursos Financieros De La “Cooperativa Juan Pío De Mora” - Reinoso Vargas, Yessenia Fabiola (2018)
Currently the economy of microentrepreneurs in Ecuador, needs who can provide capital to serve their business, so these people are in the need to apply for loans to savings and credit cooperatives, which are the most facilities they are given at the time of access to one, as it is in the case of the City of Caluma where there are Cooperatives that provide their members with loans for working capital, and this is how the public sees the need to open accounts in these cooperatives so that in a short term they can access the benefits of the loans offered by them. As a whole, savings and credit cooperatives tend to offer higher interest rates in savings accounts, less charges and lower loan rates. But in order for these savings and credit cooperatives to provide economic resources to their members they must attract new members every year that can facilitate the recourse to these institutions, which in turn is managed and lent to their clients so that they can be invest in their small businesses, knowing in advance that savings and credit cooperatives live on this provision of service as is the financial service, in which the money they receive is invested by granting loans and thus obtain income so that the institution can subsist There is no point in cooperatives capturing many resources from their partners and new partners if they can not place this resource in loans at the end.